Mahathir as the Prime Minister: Peak of “Paternalistic Leadership” In Malaysia - Jaes, Lutfan; Razali, Nurul Aimi; Mohamad Suhaimy, Khairul Azman (Res Militaris, 2023)
This article attempts to describe Mahathir in the style of paternalistic leadership in the system of governmental value in Malaysia. It is traced through the influence of local wisdom which is believed to form the leadership character of the 7th Malaysian Prime Minister. The initial stance of this article was taken with reference to a previous study when Mahathir took office as the 4th Prime Minister of Malaysia. The analysis method is content analysis by describing 12 selected speech and media texts of Mahathir over a one-year period. The analysis will observe the value of paternalistic leadership in the values of “Work Ethics”, “Communalism”, “Authority Orientation”, and “Familism”. These four values were chosen because they are often discussed by scholars as the values underlying the Asian leadership style. The data is encoded manually. The result of this study is an explanation of paternal values of Mahathir in governing will be obtained. In conclusion, the paternalistic leadership in Malaysia has reached its peak when the skills of a statesman are still in demand. Mahathir not only guided the new community free from colonialism and brought it forward with mental and physical preparation to overcome the global challenges of the 20th century, he also led and continued the works related to the “relaxation” of the past leadership. Most importantly, it is incorporated indirectly into the local wisdom of the community with some manipulation of values to suit the current needs.